Valoración del hematocrito, hemoglobina e índices hematimétricos para determinar la anemia en los niños y niñas de sexto año de educación básica de la escuela “javier sáenz” de la parroquia punín del cantón riobamba, provincia de chimborazo en el periodo 2011 – 2012 - Vaca Vicuña, Adriana Isabel (2013)
The topic, “Valuation of the Hematocrito, Hemoglobin and Index Hematimétricos to determine the Anemia in the children and girls of sixth year of basic education of the school “Javier Sáenz” of the rural community Punín of the canton Riobamba, province of Chimborazo in the period 2011-2012,” The main objective responds to the necessity of valuing the hemoglobin levels and hematocrito in the children of the establishment, since the inferior levels of the normal they can produce anemia and the cause can be for bad nutritious habits, and they are carried out it in an educational center since the anemia affects considerably in the school acquiesce or in process teaching-learning, the methodology used in the investigation was deductive - inductive, by means of a descriptive-explanatory study